Terrorism and Global Power Systems - Junaid, Shahwar (Karachi Oxford University Press, 2005)
This book discusses the origins of terrorism and the use of violence as a tool for political, social and economic change by various forces thorughtout the world. The author draws upon historical trends as well as rising terrorist activity in the world since 1980. The book also examines global power systems, including international security.
Include Appendix, Bibliography and Index
Keywords: Terrorism. -- Security, International